A review on laminar-to-turbulent transition of nanofluid flows - ÖZDEMİR, MEHMED RAFET (My University, 2022)
Nanofluids have emerged as powerful instruments in heat transfer applications due to their improved thermophysical properties. Additionally, many heat transfer equipments are started to be operated within the range of transitional flow regions in the advances in thermal management enhancement techniques. However, up to date, the friction factor and heat transfer coefficient features of nanofluids within the transitional flow regions and the effect of nanoparticle addition into the base fluid on the laminar-to-turbulent transition characteristics are still not understood clearly with contradictory published results. At this point, this paper comprehensively reviews the studies dealing with the nanofluid flow within the transitional flow regions for internal flow applications. After the presentation of applications of nanofluid flow in the transitional flow regions, the nanofluid properties such as nanoparticle type and concentration and base fluid type in the reviewed studies are given in detail. The pressure drop and heat transfer features of nanofluid flow within the transitional flow regions are distinctly identified and discussed for internal flows. The effect of the nanoparticle addition into the liquid on the transition onset is discussed with results from different research groups. A complete evaluation, challenges and further studies are proposed based on available results in the literature.
Keywords: Kimya; Analitik Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Analytical Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; TERMODİNAMİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); KİMYA, ANALİTİK; Temel Bilimler (SCI); KİMYA, FİZİKSEL; THERMODYNAMICS; ENGINEERING; Engineering, Computing & Technology (ENG); CHEMISTRY, ANALYTICAL; CHEMISTRY; Natural Sciences (SCI); CHEMISTRY, PHYSICAL; Yüzeyler ve Arayüzler; Yüzeyler, Kaplamalar ve Filmler; Genel Mühendislik; Mühendislik (çeşitli); Fiziksel ve Teorik Kimya; Kimya (çeşitli); Genel Kimya; Filtrasyon ve Ayırma; Fizik Bilimleri; Surfaces and Interfaces; Surfaces, Coatings and Films; General Engineering; Engineering (miscellaneous); Physical and Theoretical Chemistry; Chemistry (miscellaneous); General Chemistry; Filtration and Separation; Physical Sciences; Nanofluid; Laminar-to-turbulent transition; Convective heat transfer; Pressure drop; CONVECTIVE HEAT-TRANSFER; WATER NANOFLUIDS; PRESSURE-DROP; ENTROPY GENERATION; DEVELOPED FLOW; PIPE; EXCHANGER; BEHAVIOR; MIXTURE; REGIME